Pengaturan Cuti Notaris dalam Keadaan Mendesak yang Hanya Dapat Dilakukan Keluarga Sedarah Garis Lurus Notaris - Ayuni, Prianggieta; Subawa, Made (University of Udayana, 2024)
Abstract : The purpose of this research is to provide knowledge and to study and analyze problems regarding notary leave arrangements in urgent situations which can only be carried out by the Notary's blood line family. This research uses normative legal research. Notary leave arrangements in urgent situations are determined in Article 28 UUJN, however there are multiple interpretations or unclear norms in the phrase